Shushanik Artashes Abrahamyan (1946 - 2015). - “Dedicated to the jubilee” - Abrahamyan , Шушаник Арташесовна (Musical Armenia, 2017)
The article is about 45 years glorious path of Muscial College after A. Babajanyan without forgetting workers who contributed to its formation starting from the first director Melanya Cholakhyan till Armen Qristaphor Harutyunyan who is still creating. All the chapters of the study, departments, musical groups formed in college are described here in more details. The achievements of both students and pedagogues, past and present generations are mentioned here. It describes both the teachings of both tutors and learners, both past and present generations. The essence of the article is about the role and importance of the college, which has been one of the leading institutions of performing arts and has an important role in the upbringing of Republic's specialized musical education.